Identifying the Physical and Mental Healthcare Needs of Opioid Treatment Program Clients. (7th June 2022) - O'Grady, Megan A.; Neighbors, Charles J.; Randrianarivony, Rina; Shapiro-Luft, Dina; Tempchin, Jacob; Perez-Cubillan, Yaberci; Collymore, David C.; Martin, Keith; Heyward, Nyasia; Wu, Morgan; Beacham, Alexa; Greenfield, Belinda
Abstract: Background: Individuals with opioid use disorder (OUD) often have significant medical and behavioral health needs that are unaddressed. Opioid treatment programs (OTP) are uniquely positioned to provide integrated services for OUD, physical and mental health but are underutilized for this purpose. This study aims to describe the physical and mental healthcare needs of OTP clients in order to inform integrated care implementation in OTPs. Method: OTP clients ( n  = 1261) in an integrated care program in the Bronx borough of New York City were assessed for mental health symptoms (e.g., anxiety, depression), chronic disease indicators (e.g., blood pressure, cholesterol), and general functioning (e.g., capability of managing healthcare needs). Results : Symptoms of anxiety, post-traumatic stress, and depression were common. Self-reported health status and level of functioning were generally poor. Heavy smoking and obesity were the most frequent physical health risks. Other chronic disease indicators (e.g., blood pressure) showed 25-46% may be at risk. Sixty percent had multiple mental health risks and 85% had multiple physical health risks. Older clients had a higher rate of hypertension and diabetes risk than younger clients. Conclusions : Integrated care programs in OTPs must be prepared to address and coordinate care for chronic mental and physical health conditions in addition to OUD.